(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Clostridium difficle is an important pathogen responsible for antibiotic associated diarrhea. Clostridium difficle associated diarrhea (CDAD) has been a drastic change in the recent times due to its increase and severity. The infection rate dramatically increased due to frequent use of broad spectrum antibiotics in patients. Hence this study was done to estimate the incidence of CDAD in hospitalized patients with diarrhea and analyze the clinical course. To estimate the incidence of CDAD in our hospital. To assess the risk factors and clinical course of the CDAD patients. In patients with antibiotic intake having diarrhea were included in the study. Their clinical picture and laboratory tests profile were obtained and were recorded using a structured questionnaire. Single stool sample were collected from 116 patients subjected to culture & ELISA. CDAD was diagnosed in all patients with stool sample positive for toxin A&B. A total of 116 patients with diarrhea were included in the study of which 17(14.6%) developed CDAD. Among the 17 patients 11(64.71%) were male patients while 6 (35.30%) were female. Majority of cases were in the age group of above 60years, H/o surgery done in majority of cases and found 7 (41.11%) undergone abdominal surgery. All the 17 patients had at least one full course of antibiotics, 5 (29.3%), even had 2-3 course of antibiotics. Common antibiotic intake was 3rd generation cephalosporin. All the 17 patients had prolonged hospital stay and had diarrhea for more than 7 days. This study shows significant presence of clostridium difficle infection in the hospital population.